Wearing compression garment after endurance exercise promotes recovery of exercise performance - Mizuno, S.; Morii, I.; Tsuchiya, Y.; Goto, K. (International Journal of Sports Medicine, 2016)
The present study examined the effects of wearing a lower-body compression garment (CG) after endurance exercise on recovery of physiological function. 18 males were divided into 2 experiments, the downhill running (n=10, DHR) experiments and the level running (n=8, LR) experiments. Subjects performed 30 min of DHR (gradient: - 10%) or LR (gradient: 0%) at 70% of VO2max with either wearing a CG (CG trial) or normal garment (CON trial) for 24 h after running. Changes in jump performance (counter movement jump; CMJ, rebound jump; RJ, drop jump; DJ), subjective feelings, circumferences of leg, and blood variables (creatine kinase, myoglobin, interleukin-6, high-sensitivity C-reactive protein) were evaluated before exercise, immediately after exercise, 1, 3 and 2 ?h following exercise. Running economy was evaluated at 24 h following exercise. CMJ height and RJ index were significantly higher in the CG trial than in the CON trial 24 h after running (P<0.05). Although changes in muscle soreness and blood variables were significantly greater in the DHR experiment than in the LR experiment, there was no significant difference between the trials in either experiment. Wearing a CG following endurance exercise facilitated recovery of jump performance under situations with severe exercise-induced muscle damage.